The Prevalence of Delirium in An Older Acute Surgical Population and Its Effect on Outcome - Jonathan Hewitt; Stephanie Owen; Ben R. Carter; Michael J. Stechman; Hui Sian Tay; Matthew Greig; Caroline McCormack; Lyndsay Pearce; Kathryn McCarthy; Phyo K. Myint; Susan J. Moug (Geriatrics, 2019)
Background: With an ageing population, an increasing number of older adults are admitted for assessment to acute surgical units. Older adults have specific factors that may influence outcomes, one of which is delirium (acute cognitive impairment). Objectives: To establish the prevalence of delirium on admission in an older acute surgical population and its effect on mortality. Secondary outcomes investigated include hospital readmission and length of hospital stay. Method: This observational multi-centre study investigated consecutive patients, ≥65 years, admitted to the acute surgical units of five UK hospitals during an eight-week period. On admission the Confusion Assessment Method (CAM) score was performed to detect delirium. The effect of delirium on important clinical outcomes was investigated using tests of association and logistic regression models. Results: The cohort consisted of 411 patients with a mean age of 77.3 years (SD 8.1). The prevalence of admission delirium was 8.8% (95% CI 6.2−11.9%) and cognitive impairment was 70.3% (95% CI 65.6−74.7%). The delirious group were not more likely to die at 30 or 90 days (OR 1.1, 95% CI 0.2 to 5.1, p = 0.67; OR 1.4, 95% CI 0.4 to 4.1. p = 0.82) or to be readmitted within 30 days of discharge (OR 0.9, 95% CI 0.4 to 2.2, p = 0.89). Length of hospital stay was significantly longer in the delirious group (median 8 vs. 5 days respectively, p = 0.009). Conclusion: Admission delirium occurs in just under 10% of older people admitted to acute surgical units, resulting in significantly longer hospital stays.